Fixed Point Results for Generalized Chatterjea Type Contractive Conditions in Partially Ordered G-Metric Spaces - Safeer Hussain Khan; Mujahid Abbas; Talat Nazir (The Scientific World Journal)
In the framework of ordered G-metric spaces, fixed points of maps that satisfy the generalized (ψ,φ)-Chatterjea type contractive conditions are obtained. The results presented in the paper generalize and extend several well known comparable results in the literature.